Analysis of novel meningococcal vaccine formulations. Issue 7 (3rd July 2017) - Zughaier, Susu M.
ABSTRACT: The protective effect of meningococcal vaccines targeting disease causing serogroups exemplified by the introduction of MenAfriVac™ in Africa, is well established and documented in large population-based studies. Due to the emergence of other meningococcal disease causing serogroups, novel vaccine formulations are needed. There is a high potential for novel nanotechnology-based meningococcal vaccine formulations that can provide wider vaccine coverage. The proposed meningococcal vaccine formulation contains spherical shaped micro and nanoparticles that are biological mimics of Niesseria meningitidis, therefore present to immune system as invader and elicit robust immune responses. Vaccine nanoparticles encapsulate meningococcal CPS polymers in a biodegradable material that slowly release antigens, therefore enhance antigen presentation by exerting antigen depot effect. The antigenicity of meningococcal vaccine delivered in nanoparticles is significantly higher when compared to vaccine delivered in solution. Preclinical studies are required to assess the immunogenicity of novel vaccine formulations. Therefore, implementing various in-vitro human immune cell-based assays that mimic in-vivo interactions, would provide good insight on optimal antigen dose, effective antigen presentation, facilitate screening of various vaccine and adjuvant combinations and predict in-vivo immunogenicity. This rapid approach is cost-effective and provides data required for the preclinical immunogenicity assessment of novel meningococcal vaccine formulations.